Basic College Mathematics (10th Edition)

Published by Pearson
ISBN 10:
ISBN 13:

Chapter 3 - Adding and Subtracting Fractions - 3.5 Order Relation and the Order of Operations - 3.5 Exercises - Page 245: 68

Answer

$\frac{1}{12}$

Work Step by Step

$(\frac{2}{3})^{2}(\frac{1}{2} - \frac{1}{8}) - \frac{2}{3}(\frac{1}{8})$ = $(\frac{2}{3})^{2}(\frac{4}{8} - \frac{1}{8}) - \frac{2}{3}(\frac{1}{8})$ = $(\frac{2}{3})^{2}(\frac{3}{8}) - \frac{2}{3}(\frac{1}{8})$ = $(\frac{4}{9})(\frac{3}{8}) - \frac{2}{3}(\frac{1}{8})$ = $(\frac{1}{3})(\frac{1}{2}) - \frac{1}{3}(\frac{1}{4})$ = $\frac{1}{6} - \frac{1}{12}$ = $\frac{2}{12} - \frac{1}{12}$ = $\frac{1}{12}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.